LDPC codes for physical layer security - Kuljanski Marić, Sonja R. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Wireless communication is ubiquitous in today’s society. Unfortunately, wireless transmission is by the nature of broadcasting suitable for eavesdropping. These links are usually secured by encryption protocols that rely on cryptographic algorithms whose security is based on complexity of calculation and inability to calculate in real time. The hypothesis in the field of information theory is that the eavesdropper has unlimited computer capabilities, and the use of common cryptographic protocols is uncertain. Instead, it is assumed that the legitimate recipient of the message has a better communication channel than the intrusion listening. Based on this physical advantage, it is possible to use random encoding schemes for the transmission of information at the physical level. These schemes function without the prior exchange of secret keys securely, so protection at this layer tends to significantly simplify key management in communication systems. At the end of the last and the beginning of this century, there was an idea that LDPC codes should be applied to protect data at the physical layer. In this paper, the Wyner model of the communication channel was used, and LDPC codes were constructed for the transmission of information through this channel. A comparison of the basic algorithm and its modification was made based on the following parameters: transmission of mutual information, bit-error rate and execution time. An algorithm for different sizes of LDPC codes was also performed based on the above parameters.